Quality of life among urban hypertensive patients - Ngoc, Tran Nguyen; Tung, Dang Thanh; Dung, Bui Van; Anh, Trinh Viet; San, Bui Van; Nam, Hoang Thi Phuong; Thanh, Nguyen Hoang; Quang, Huy Dinh; Tran, Thien Van (Intelektual Pustaka Media Utama, 2023)
Hypertension is a leading risk factor for major chronic illnesses. This study investigated the quality of life (QOL) of hypertensive patients in an urban setting and evaluate related factors. A cross-sectional study on 220 hypertensive patients was performed in Hanoi, Vietnam. Short-form 12 version 2 (SF12-v2) was used to assess QOL. Sociodemographic and clinical characteristics were also obtained. Multivariate regression was utilized to explore the related factors with patients’ QOL. The mean physical health (PCS-12) and mental health (MCS-12) scores were 43.3 (SD=7.9) and 56.3 (SD=6.5), respectively, Higher age was related to a lower PCS-12. People living in low-population-density settings have a higher MCS-12 score than those living in high-density settings. Increasing comorbidity and medication reduced both component scores. Patients participating in social activity had the MCS-12 score higher than those not participating. This study found a moderate level of health-related quality of life (HRQOL) in hypertensive patients regardless of treatment progress. Regular screening and controlling comorbidities, as well as motivating active employment and social activities involvement, are the potential to enhance the HRQOL of this population.